Komunikasi Artifaktual sebagai Media Dakwah: Studi Club Motor Bikers Subuhan Lampung Melawan Stigma Negatif Geng Motor - Naufal Maskuri, M. Ibnu; Yanti, Fitri (LP2M UIN Sunan Kalijaga, 2023)
Lampung province is notorious for the rampant criminality of begal and the anarchy of a number of motorcycle gangs that disturb the community. The emergence of motorcycle clubs is a frightening specter for the people of Lampung. The Bikers Subuhan Lampung Motorcycle Club is present to erase this bad stigma. Its movement in da'wah activities is interesting to study. The purpose of this article is to analyze the role of artifactual communication as a means of dakwah for the Subuhan Lampung Bikers Motorcycle Club. This research uses a qualitative approach, collecting data through interview techniques, observation, and documentation. Then the data that has been collected is analyzed using the principles of qualitative data analysis (Miles and Huberman). Artifactual communication as a medium of da'wah for Subuhan Lampung Bikers Motor Club becomes its own medium for inviting audiences to join and carry out their da'wah activities. [Provinsi lampung terkenal dengan maraknya kejahatan kriminal begal dan anarkisnya sejumlah anggota club motor yang membuat masyarakat terganggu. Munculnya club motor menjadi momok menakutkan bagi masyarakat lampung. Club Motor Bikers Subuhan Lampung hadir untuk menghapus stigma buruk tersebut. Pergerakannya pada aktivitas dakwah menarik untuk diteliti. Tujuan dari artikel ini adalah untuk menganalisis peran komunikasi artifaktual sebagai media dakwah Club Motor Bikers Subuhan Lampung. Penelitian ini menggunakan pendekatan kualitatif, pengumpulan data melalui teknik wawancara, observasi dan dokumentasi. Kemudian data yang sudah terkumpul dianalisis menggunakan prinsip analisis data kualitatif Miles dan Huberman. Komunikasi artifaktual sebagai media dakwah Club Motor Bikers Subuhan Lampung menjadi media tersendiri dalam mengajak khalayak untuk bergabung dan melakukan aktivitas dakwah mereka.]